Zubiri’s notes about justice and solidarity - Jiménez Retana, Randall (2020)
This article explores the constructs of justice and solidarity, from the perspective of Xavier Zubiri.  Particularly, this work draws on the authors that illuminate these concepts, such as Ignacio Ellacuria and Emmanuel Mounier.  It also establishes how solidarity and justice are natural features in the human being. Therefore, human life has to be presence and commitment, which implies being prudent in actions, promoting the development of the community.